Edukasi Kualitas Air Minum Yang Aman Bagi Mahasiswa - Suhanto, Rhesti Nurlina; Westari, Dwianti; Ilman, Syaeful (Universitas Negeri Gorontalo, 2025)
The quality of drinking water is a critical factor that impacts an individual's health. Contaminated drinking water can serve as a medium for disease transmission and lead to the decline in organ function. The lack of public awareness about the standards for safe drinking water has prompted educational initiatives for the students of Instrumentation and Control Engineering Technology program at Politeknik Negeri Indramayu. This initiative included a presentation, interactive discussions, and an evaluation. Following their participation, most students gained a better understanding of the criteria for safe drinking water and became more aware of the importance of monitoring water quality. They also expressed interest in developing technologies to detect drinking water quality as an innovative solution for public health. Furthermore, implementation of this activity is expected to accelerate the adoption of drinking water quality monitoring technologies, ultimately reducing the risk of waterborne diseases.